Biological function of d-tryptophan: a bibliometric analysis and review - Wang, Fei; Du, Runyu; Shang, Yunxiao (Frontiers in Microbiology, 2025)
Backgroundd-Tryptophan is recognised for its unique physiological properties. In this study, we aimed to explore the dynamic trends and emerging topics in d-tryptophan research to offer fresh perspectives for future studies.MethodsEmploying bibliometric analysis, we examined the literature on d-tryptophan indexed in the Web of Science Core Collection from January 1987 to December 2023. The “Bibliometrix” R package and CiteSpace were utilised for data processing.ResultsAnalyses of 865 publications revealed 2209 keywords, 4068 authors, 2094 institutions, and contributors from 302 regions. The USA was at the forefront of publications concerning d-tryptophan, but the European Journal of Pharmacology, Journal of Biological Chemistry, and Journal of Medicinal Chemistry were notable for their contributions, co-citations, and impact, respectively. This literature review reveals that since 1987, studies have developed from a focus on d-tryptophan metabolism to the exploration of its functions in organic and medicinal chemistry and food science. Recent findings highlight the potential of d-tryptophan as a non-nutritional sweetener and food preservative as well as its role in inhibiting the growth of bacterial biofilms. Additionally, its immunomodulatory properties are being investigated in relation to allergic diseases. Furthermore, d-tryptophan plays a role in the therapy of atherosclerosis, osteoporosis, tuberculosis, and cancer.ConclusionThe results of bibliometric analysis highlight that future research should focus on the biological functions of d-tryptophan as a food preservative and its use in immunomodulation and drug development, providing strong guidance for future research.